Protection of Petroleum Pipeline Carbon Steel Alloys with New Modified Core-Shell Magnetite Nanogel against Corrosion in Acidic Medium - Gamal A. El Mahdy; Ayman M. Atta; Amro K. F. Dyab; Hamad A. Al-Lohedan (Journal of Chemistry)
New method was used to prepare magnetite nanoparticle based on reduction of Fe(III) ions with potassium iodide to produce Fe3O4 nanoparticle. The prepared magnetite was stabilized with cross-linked polymer based on 2-acrylamido-2-methylpropane sulfonic acid (AMPS to prepare novel core-shell nanogel. In this respect, Fe3O4/poly(2-acrylamido-2-methylpropane sulfonic acid) (PAMPS) magnetic nanogels with controllable particle size produced via free aqueous polymerization at 65°C have been developed for the first time. The polymer was crosslinked in the presence of N,N-methylenebisacrylamide (MBA) as a crosslinker and potassium peroxydisulfate (KPS) as redox initiator system. The structure and morphology of the magnetic nanogel were characterized by Fourier transform infrared spectroscopy (FTIR) and transmission and scanning electron microscopy (TEM and SEM). The effectiveness of the synthesized compounds as corrosion inhibitors for carbon steel in 1 M HCl was investigated by various electrochemical techniques such as potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The results showed enhancement in inhibition efficiencies with increasing the inhibitor concentrations. The results showed that the nanogel particles act as mixed inhibitors. EIS data revealed that Rct increases with increasing inhibitor concentration.